Caregiving experiences and expectations of parents with in-school children with intellectual disability in Ghana. (January 2020) - Opoku, Maxwell Peprah; Nketsia, Williams; Banye, Mabel A.; Mprah, Wisdom K.; Dogbe, Joslin A.; Badu, Eric
Abstract: Background: The literature suggests that there are challenges faced by parents of children with intellectual disabilities (ID), which have resulted in calls for support services to be made available to parents and their children with ID. Although regular schools in Ghana are unable to admit students with ID, it is believed that special schools have the necessary facilities to support parents and their children with ID. However, little has been documented on the experiences and expectations of parents whose children with ID are enrolled in a special school. Method: In this qualitative study, one-on-one semi-structured interviews were conducted with purposively recruited parents ( n = 20) from the second most populous city in Ghana to explore their caregiving experiences and expectations regarding the education of their school-going children with ID. Results: Although the parents acknowledged that access to education has some benefits, such as the protection of their children with ID from negative societal attitudes and a reduction of their caregiving burden, they had low expectations for their children's education. Furthermore, the parents encountered considerable challenges in catering for their children with ID, such as financial problems and limited access to caregiving skills. Conclusion: There is a need to intensify efforts at public education in relation to disability acceptance as well as to develop formidable social support systems.